Determinar el potencial turístico del cantón Saquisilí - Pallo Chicaiza, Holger Xavier (2023)
Ecuador is the country of mega diversity and possibly one of the richest on the planet, because thanks to its great contrasts, in its small territory combines 4 natural regions that offers an immensity of soils, climate, mountains, paramos, beaches, islands and jungle, which at the same time are home to thousands of species of flora and fauna. The Saquisili canton is known as the land of the merchant is located in the province of Cotopaxi, is one of the sites that can become a potential tourism and socio-economic development source, its 4 parishes have different natural and cultural attractions the same that can be exploited in an appropriate manner. The present project was carried out in the Saquisili Canton with the objective of determining the tourism potential, for which three specific objectives were proposed to carry out the project. In the first objective, field trips were made in order to observe the conditions of the attractions of the canton, to make the inventory of attractions with the MINTUR cards shows that there are 3 new cultural attractions in the parishes of Saquisili and Chantilin giving as a result 24 natural and cultural attractions by updating the inventory, indicating that it has progress in tourism in each parish of the canton Saquisili. The second objective is carried out through surveys of tourists visiting the canton, then an interview was conducted with ING: Diego Vargas to identify and analyze the tourism potential of the attractions. With the results obtained from the interview and survey, a SWOT matrix was created to identify the strengths, opportunities, weaknesses and threats that the canton has. This was used to analyze the MEFE and MEFI matrices, based on the Sandoval 2006 matrix of potential indicators, arriving at the evaluation of the potential of the Saquisili canton of the identified parishes. As a result, the parish of Cochapamba has a high tourism potential. Finally, in the third objective, an academic article was prepared as a means of dissemination of the completed project, which will be published in the journal RENPYS to publicize the results achieved through the research conducted in the canton.